Henry Woodhouse collection relating to George Washington - Woodhouse, Henry, 1884-
Correspondence, deeds, wills, testaments, indentures, bonds, land grants, surveys, maps, plats, financial and legal records, clippings, and other papers relating principally to George Washington, the Washington family, and its descendants. Includes papers relating to the Washington family estate in Wakefield, Westmoreland County, Va. Individuals represented include Francis Lightfoot Lee, Richard Henry Lee, Augustine Washington, George Corbin Washington, H.A. Washington, Lawrence Washington, Robert James Washington, and William Augustine Washington.
In part, transcripts and photocopies.
Editor and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Lee, Francis Lightfoot, -- 1734-1797.; Lee, Richard Henry, -- 1732-1794.; Washington, Augustine, -- approximately 1694-1743.; Washington, George, -- 1732-1799.; Washington, George, -- 1732-1799 -- Family; Washington, George Corbin, -- 1789-1854.; Washington, H. A. -- 1820-1858.; Washington, Lawrence, -- 1718-1752.; Washington, Robert James, -- 1841-; Washington, William Augustine, -- 1757-1810.; Washington family; Land grants -- Virginia -- Westmoreland County; Wakefield (Westmoreland County, Va.); Authors; Editors